Influence of Socio-Economic Background on Social Adjustment Development of Adolescents with Hearing Impairment in Oyo State. (Global Journal of Human-Social Science, 2015)
This paper investigated the influence of socio-economic background on social adjustment development of adolescents with hearing impairment in Oyo state. The study used 48 participants comprised of 24 males and 24 females who were purposely selected for the study. The research was based on simple descriptive survey research method. Two research instruments were used to gather data for the study. The two sets of questionnaire are Socio-Economic Questionnaire (SEQ) and Social Adjustment Questionnaire (SAQ). One hypothesis was tested and the result showed that adolescents with hearing impairment from high socioeconomic background socialized and adjusted well than their counterparts from low socioeconomic background. The paper recommended among others that awareness program should be mounted on the news media to parents and other stakeholders by professionals on the care and needs of the adolescents with hearing impairment.
Keywords: socio-economic; social adjustment; development; adolescent; hearing impairment